Journalism and comprehension: a bet on the science to come - Moura Klautau, Carolina; Künsch, Dimas A.; López (traductor), Franco (Folios, revista de la Facultad de Comunicaciones y Filología, 2022)
The paper proposes comprehension as a method of building knowledge, thus defending a dialogical movement that cuts across both the universe of the sciences and different cognitive universes, in relationships with one another that are kind of close, with no hierarchies. It is understood that this dialogical or pluralogical game assumes the emergent character and urgency of a true Zeitgeist of contemporary times. The authors’ old and no less current criticism of positivism solidifies the notion of the existence of plural, inter- and undisciplinary forms of knowledge, making room for the understanding of journalism itself as a singular kind of knowledge that is linked to the immediate present, and is also necessary and urgent, especially in times of crisis of different shades, as in our historical time. An approach that is believed pertinent and useful in daily journalistic practice, in the context of comprehension: this is to be achieved as a result of this rapid foray into the world of epistemology.